Nanosecond Switching in Superlattice-Like GeTe/Sb Thin Film for High Speed and Low Power Phase Change Memory Application. (28th December 2016) - Hu, Yifeng; Zhu, Xiaoqin; Zou, Hua; You, Haipeng; Zhai, Liangjun; Song, Sannian; Song, Zhitang
Abstract : Superlattice-like GeTe/Sb thin films were investigated for their potential application in phase change memory. Compared with monolayer GeTe thin film, GeTe/Sb thin film has lower crystallization temperature (208°C), crystallization activation energy (2.38 eV) and thermal conductivity (0.15 W/(m·K)). In GeTe/Sb thin film, GeTe and Sb phases exist independently. The superlattice-like structure is observed even after annealing at 250°C for 10 min. The shorter phase change time is achieved for GeTe/Sb thin film (4.3 ns). The GeTe/Sb-based phase change memory devices show an operation speed of as fast as 9 ns and a low RESET operation power of 4.09 × 10 −13 J.